PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII UPTD SMP NEGERI 1 KEC. KAPUR IX - FAUZAN . (Departemen Matematika, 2021)
This study aims to see how the influence of motivation on mathematics learning outcomes of class VII students of UPTD SMP Negeri 1 Kec. Kapur IX. Learning outcomes good and rewarding comes to students when learning motivation both from whitin and from outside the great student. The study is a descriptive quantitative research whit a correlational approach to influence between variables and other variables. The data analysis shows that the coefficient value of correlation rcount (0,926) is greater that the rtable (0,273) at significant of 5% and has an impact of 85%, which means influence the learning motivation to learning outcomes mathematics is 85% and the rest are affected by other uninvolved variables in the study. Keywords – Descriptive Research, Learning Motivation, Learning Outcomes